HUBUNGAN KAPABILITAS TEKNOLOGI INFORMASI TERHADAP KINERJA PERUSAHAAN (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2018 dan 2019) - Hania Anis Kayfiyati; Paulus Th. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2022)
This study aimed to examine the effect the superior information technology capabilities on firm performance of listed companies on the Indonesia Stock Exchange (IDC). The study was a case-control model where the case sampel was Top Indonesian IT-TELCO during 2018 to 2019 whole the contril sample (non IT-TELCO) was firms in the same sector which had almost similar asset. Fifty four54 companies were obtained that match the criteria to be used as research samples.Multiple linear regression adopted to examine the relationship model. The results of this study       reveal that superior information technology capabilities had a significant positive relationship on firm performance.